The Influence of Management Capability, Staff Competence, and Waiting Time on Revisit Intention at Dental Clinic X with Patient Satisfaction as a Mediating Variable - Lismawati Lismawati; Zoel Hutabarat (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the effects of management capability, staff competence, and waiting time on patient revisit intention at Dental Clinic X, with patient satisfaction as a mediating variable. A quantitative explanatory design was applied using a structured questionnaire distributed to patients who had visited the clinic more than once. A total of 213 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that management capability and staff competence have positive and significant effects on patient satisfaction. Patient satisfaction also has a positive and significant effect on revisit intention. Management capability has a direct positive effect on revisit intention, while staff competence and waiting time do not have significant direct effects. The mediation test indicates that patient satisfaction mediates the effects of management capability and staff competence on revisit intention, but does not mediate the effect of waiting time. These findings highlight the importance of managerial quality and staff competence in strengthening patient satisfaction and encouraging revisit intention in dental health services.